Parents' prejudices or own religious orientation of Pakistani children: determinants of achievement-related prejudices for opposite gender and sect and their relation with mental health. Issue 1 (2nd January 2021) - Khan, Aasia Alam; Malik, Jamil A.; Musharraf, Sadia; Lewis, Christopher Alan
ABSTRACT: The present study examined the role of parents' prejudices and their children's own religious orientation in the formation of children's prejudices against the opposite gender and sect. A total of 280 children including 104 (36%) girls were recruited from various schools. Children age range from 12 to 18 years with mean ± SD = 14.60 (1.42) years. Parents of the children (including 175 fathers and 113 mothers) were approached at their homes. Based on the conceptualisation of the study, parallel models addressing gender and sectarian ingroup-outgroup classification were developed and estimated. The study tested, confirmed, and validated the cognitive-developmental model addressing the underlying mechanism for shaping the religious orientation of children as a consequence of parents' prejudices and its role in the mental health of children. The results supported the conceptual model of the study elaborating on the underlying mechanism of the relationship among parents' and children's prejudices, and children's religious orientation in the development of depression and anxiety in children. Suggestions for further research are provided.